Use of Over-the-Counter Products in Lebanese Adults with Cardiovascular Disease - Sheikh-Taha, Marwan; El-Halabi , Celia; El-Harake, Katia (Journal of Pharmacy and Nutrition Sciences, 2021)
Background: While selling over-the-counter (OTC) products in pharmacies is convenient to individuals and can be beneficial, it might potentially cause harm. We hereby describe the patterns of OTC product consumption amongst adults with cardiovascular disease (CVD) in Lebanon and the potential interactions with prescription medications and patient diseases. Methods: This was a cross-sectional study in the setting of nine community pharmacies across different governorates of Lebanon. Data of interest were collected from adult patients with CVD history through face-to-face interviews using a short questionnaire. Results: Out of 201 adult patients included in the study, 190 (94.5%) were using at least one OTC product, with a mean of 3.2 ± 2.4 per patient (range of 1 to 12 products). The proportion of patients taking analgesics was the greatest (81.1%), followed by those taking vitamins (48.8%), minerals (29.9%), and herbal products (13.9%). Several potentially harmful OTC product- drug or -disease interactions were identified. Only 65.3% of OTC users reported obtaining information about the used products from healthcare professionals (HCPs), and 35.3% did not disclose the use of the products to their HCPs. Conclusion: The use of OTC products was highly prevalent among patients with CVD with potential interactions with prescription medications and patient diseases. In order to ensure optimal patient outcomes, clinicians are strongly encouraged to inquire about OTC product use and counsel patients about the risks and benefits associated with such products.